2014
DOI: 10.1016/j.bbrc.2014.03.035
|View full text |Cite
|
Sign up to set email alerts
|

MiR-92a regulates viability and angiogenesis of endothelial cells under oxidative stress

Abstract: Oxidative stress contributes to endothelial cell (EC) dysfunction, which is prevalent in ageing and atherosclerosis. MicroRNAs (miRs) are small, non-coding RNAs that post-transcriptionally regulate gene expression and play a key role in fine-tuning EC functional responses, including apoptosis and angiogenesis. MiR-92a is highly expressed in young endothelial cells in comparison with senescent endothelial cells, which exhibit increased oxidative stress and apoptosis. However, the impact of miR-92a treatment on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Wang et al reported that miR-126, the endothelial specific miRNA, enhances the proangiogenic actions of VEGF and FGF and promotes blood vessel formation by repressing the expression of Spred-1, an intracellular inhibitor of angiogenic signaling [43]. Besides, members of the miRNA-17-92 cluster also exhibit a cell-intrinsic antiangiogenic function in ECs [42, 66, 67]. For example, pre-miR-92a treatment improves HUVEC viability and preserves angiogenic capacity under oxidative stress, at least partially through the downregulation of PTEN expression [42].…”
Section: Mirnas and Vascular Agingmentioning
confidence: 99%
“…Wang et al reported that miR-126, the endothelial specific miRNA, enhances the proangiogenic actions of VEGF and FGF and promotes blood vessel formation by repressing the expression of Spred-1, an intracellular inhibitor of angiogenic signaling [43]. Besides, members of the miRNA-17-92 cluster also exhibit a cell-intrinsic antiangiogenic function in ECs [42, 66, 67]. For example, pre-miR-92a treatment improves HUVEC viability and preserves angiogenic capacity under oxidative stress, at least partially through the downregulation of PTEN expression [42].…”
Section: Mirnas and Vascular Agingmentioning
confidence: 99%
“…Recent research has shown that the abnormal expression of miRNAs is closely related to the formation of HCC [17]. Another research reported that miRNAs regulate angiogenesis [18]. These differentially expressed miRNAs may be new antiangiogenesis targets for HCC [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that the transplantation of stem cells into the heart can promote cardiac repair via paracrine effects [37]. Stem cells can secret extracellular vesicles (EV) [8, 9], which carry noncoding RNAs, including microRNA (miRNA) and long noncoding RNA (lncRNA), which control gene expression via posttranscriptional repression [1012] or epigenetic regulation [13]. In stem cells, noncoding RNAs have been show to play critical roles in modulating cell differentiation, proliferation, and survival [14, 15].…”
Section: Introductionmentioning
confidence: 99%